EVALUATION OF ISLAMIC EDUCATION LEARNING AT HIDAYATUL MUSTAFIDIN HIGH SCHOOL - Ashif Az Zafi; Anik Sri Widayati (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
This study aims to determine how the evaluation of Islamic Religious Education learning at SMA Hidayatul Mustafidin. The strategy used in implementing the learning evaluation and the results of the evaluation of learning Islamic Islamic Religious Education learning at SMA Hidayatul Mustafidin. In the research process the author uses a qualitative approach. The data collection is done by means of obsevation, interviews, and literature studies. the results of the research in general can be obtained that application of the evaluation of Islamic Religious Education learning at SMA Hidayatuk Mustafidin in addition to written methods such as daily test, midterm assessments, end of semester assessments, also seen the behavior of students so that when students behave less well, guidance will be given. It can be seen from the student activity forum such as tambourine, scouting, and student council activites. The impact obtained by students is expected to be able to behave well. Keywords: Evaluation; Learning; Islamic Education.